WORD ORDER PATTERNS IN ENGLISH AND UZBEK SENTENCES - Ravshanbekova Laylo; Kosheva Dilrabo Khudoyorovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper examines the word order patterns in English and Uzbek sentences, focusing on their structural, functional, and typological characteristics. The study reveals that while English follows a fixed Subject–Verb–Object (SVO) structure, Uzbek demonstrates a flexible Subject–Object–Verb (SOV) pattern. The research also discusses how grammatical relations, emphasis, and communication goals influence word order choices in both languages.